Glucose responses to acute and chronic exercise during pregnancy: a systematic review and meta-analysis. Issue 21 (18th October 2018) - Davenport, Margie H; Sobierajski, Frances; Mottola, Michelle F; Skow, Rachel J; Meah, Victoria L; Poitras, Veronica J; Gray, Casey E; Jaramillo Garcia, Alejandra; Barrowman, Nick; Riske, Laurel; James, Marina; Nagpal, Taniya S; et al.
Abstract : Objective: To perform a systematic review and meta-analysis to explore the relationship between prenatal exercise and glycaemic control. Design: Systematic review with random-effects meta-analysis and meta-regression. Data sources: Online databases were searched up to 6 January 2017. Study eligibility criteria: Studies of all designs were included (except case studies and reviews) if they were published in English, Spanish or French, and contained information on the population (pregnant women without contraindication to exercise), intervention (subjective or objective measures of frequency, intensity, duration, volume or type of acute or chronic exercise, alone ('exercise-only') or in combination with other intervention components (eg, dietary; 'exercise+cointervention') at any stage of pregnancy), comparator (no exercise or different frequency, intensity, duration, volume and type of exercise) and outcome (glycaemic control). Results: A total of 58 studies (n=8699) were included. There was 'very low' quality evidence showing that an acute bout of exercise was associated with a decrease in maternal blood glucose from before to during exercise (6 studies, n=123; mean difference (MD) −0.94 mmol/L, 95% CI −1.18 to −0.70, I 2 =41%) and following exercise (n=333; MD −0.57 mmol/L, 95% CI −0.72 to −0.41, I 2 =72%). Subgroup analysis showed that there were larger decreases in blood glucose following acute exercise in women with diabetes (n=26; MD −1.42, 95% CI −1.69 to −1.16, I 2 =8%) compared with those without diabetes (n=285; MD −0.46, 95% CI −0.60 to −0.32, I 2 =62%). Finally, chronic exercise-only interventions reduced fasting blood glucose compared with no exercise postintervention in women with diabetes (2 studies, n=70; MD −2.76, 95% CI −3.18 to −2.34, I 2 =52%; 'low' quality of evidence), but not in those without diabetes (9 studies, n=2174; MD −0.05, 95% CI −0.16 to 0.05, I 2 =79%). Conclusion: Acute and chronic prenatal exercise reduced maternal circulating blood glucose concentrations, with a larger effect in women with diabetes.